The relationship between body composition and aerobic energy expenditure during technical performance of kendo - Sancassani, Andrei [UNESP]; Pessôa Filho, Dalton Müller [UNESP]; Moreira, Pedro V. S.; Nagamine, Kazuo; Neiva, Cassiano M. [UNESP]; Verardi, Carlos E. L. [UNESP] (My University, 2017)
Background and Study Aim: There is no reasonable enough scientific knowledge about the aerobic energy expenditure from practicing kendo techniques. Therefore, this study aim is an aerobic energy expenditure (Ė) during the practice of kendo techniques. We verify the hypothesis that Ė, metabolic rate (as metabolic equivalent unit, MET) and the rate of carbohydrate oxidation are proportional in magnitude to the amount of regional and whole-body fat-free mass (FFM) of the kendo practitioners. Material & Methods: Ten male participants (29.0 ±7.6 years, 82.0 ±14.2 kg, 174.4 ±7.5 cm) underwent body composition evaluation by dual-energy X-ray absorptiometry (DXA), progressive tests to determine O2max, and performance of kendo protocol, with 11 warm-up and 31 kendo techniques (waza). During the protocol, gas exchange were measured using K4b2 (COSMED®). Based on O2 and CO2 data, the Ė was calculated using (Ė = 3.941•O2 + 1.106•CO2) and converted to MET, assuming the constant (= 4.184 kJ•kg-1•h-1). Pearson coefficient (r) tested the correlations between regional and whole-body composition data with the values obtained for Ė during warm-up and waza. A significance level of p≤0.05 was considered. Results: The peak aerobic rate during warm-up and waza reached 7.5 ±1.4 (METs) and 8.0 ±1.9 (METs), respectively. The FFM of the trunk, lower and upper limbs correlated with total Ė (76.3 ±13.2 kcal) during warm-up, with (r) ranging from 0.72 to 0.92, as well as with total Ė (218.5 ±34.8 kcal) for the execution of entire protocol (r = 0.67 to 0.75). Conclusion: The practice of kendō is classified as vigorous exercise requiring high cost of aerobic energy, which is higher in practitioner with larger regional FFM.
Keywords: Fat-free mass; Kakari-geiko; Martial art; Metabolic equivalent; Oxygen consumption